PENAMBATAN SENYAWA KOMPONEN TANAMAN KUMIS KUCING (Orthosiphon stamineus Benth) SEBAGAI DIURETIK MENGGUNAKAN METODE DOCKING - Fatwa Hasbi; Saeful Amin; Tita Nofianti (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2018)
Orthosiphon Benth Stamineus is an herbal remedy that has a diuretic effect empirically. The 98’s chemical compounds from orthosiphon has been docking into some receptors ; 1Z9Y receptor with Furosemide as comparator ligand (native), 3HS4 receptor with Acetazolamide as comparator ligand (native) and 3VHU receptor with Spironolactone as comparator ligand (native). The results showed that litospermat acid 1 has -120,0670 kcal of energy which is the lowest bond energy to the receptor 1Z9Y, Dikafeoil tartaric has -107,0110 kcal of energy which is the lowest bond energy to the receptor 3HS4, but for 3VHU receptors did not get any lowest bond energy from 98’candidates compared with the energy of spironolactone is -114,5740 kcal. Ortosifonon C as component of chemical compound java’s tea which according to the literature has a diuretic effect, evidanced the data it has -91,2897 kcal to bind with 1Z9Y and -79,4270 kcal to bind with 3HS4, thus energy are lower than the native ligand (Acetazolamide). Lower energy to bind with the receptor it can makes more stable for the binding. The results of visualization showed thus are has similarities of the hydrogen bonds between the compound Litospermat acid I, Dikafeoil tartaric and Ortosifonon C with native ligand. So that 3 of chemical compounds is predicted to have the highest potential as a diuretic.